The importance of controlling transcription elongation at coding and non-coding RNA loci - Scruggs, Benjamin S. (Cold Spring Harb Symp Quant Biol, 2015)
Here we discuss current paradigms for how transcription initiation and elongation control are achieved in mammalian cells, and how they differ at protein-coding mRNA genes vs. non-coding RNA (ncRNA) loci. We present a model for the function of ncRNAs wherein the act of transcription is regulatory, rather than the ncRNA products themselves. We further describe how the establishment of transcriptionally engaged, but paused, RNA polymerase II impacts chromatin structure around divergent transcription start sites, and how this can influence transcription factor binding and mRNA gene activity in the region.